Compressibility of palm kernel oil-based polyurethane foam/resin as alternative method for ground improvement / Mohd Azwan Salleh - Salleh, Mohd Azwan (2016)
Ground improvement methods are the best alternatives to enhance the soil properties in order to ensure that unsuitable site locations which have poor soil conditions can be developed for future development. Injection of light weight material such as polyurethane foam is found to be one of best alternatives that provide low-cost and reliable techniques for ground improvement. The use of petroleum-based polyurethane is widely used in geotechnical application but nowadays it is seen to become more expansion due to high depleting rate and high cost of production. Instead of using the polyurethane foam/resin from petroleum-based, this study is focusing on performance of polyurethane from palm kernel oil-based as new alternative for ground improvement method. The plam kernel oil-based polyurethane foam/resin is anticipated to be more economical since it used the renewable source, where it does not lead to permanent depletion of resources which has a limited global availability. The objectives of this study are to determine the expansion and compressibility of the palm kernel oil-based polyurethane with different mixing ratio. The samples were test using rowe cell test to determine the compressibility, swelling index and preconsolidation pressure of the polyurethane. The result of the findings shows that the expansion and compressibility of the palm kernel oil-based polyurethane foam/resin is depending on the mixing ratio of isocynate and polyol liquid. The polyol acts as an expansion agent whilst isocynate strengthens the mixture of the polyurethane. The compressibility index of PKO-BPU is higher than chemical based polyurethane but low in expansion.